Waterborne Diseases: A profile analysis based on literature (Research, Society and Development, 2023)
Knowledge about population’s health situation is essential for the improvement of health surveillance practices, in an integrated manner with the services, aiming at early detection of the occurrence of diseases, for the timely application of control and prevention measures. So, this study aimed to analyze the waterborne diseases (DVH) epidemiological profile, based on scientific literature. This is an integrative literature review based on PVO strategy to construct the research question - "how has the scientific literature described the waterborne diseases epidemiological profile?" and select the indexed and alternative terms in the Health Sciences Descriptors (DeCS), Medical Subject Headings (MESH) and Embase Subject Headings (Emtree), using Boolean operators AND and OR to constitute the search expression in the Latin American and Caribbean Health Sciences Information Literature (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) databases via Pubmed,  Elsevier Medical Base (EMBASE), Scopus and Web of Science (WOS). Inclusion criteria were considered as fully available studies published in the period from 2018 to 2022; and articles that were not in the languages in Portuguese, English or Spanish were excluded. A total of 317 studies were found, of which 32 were selected for full reading, which consolidate the findings related to DVH, taking into account the different forms of transmission and etiological agents of the diseases, bringing the main diseases monitored by the Unified Health System in Brazil, especially when we consider the National Agenda of Priorities in Health Research.